Strategy analysis of directoring of the ketoprak event at LPP RRI Semarang - Sri Hastuti (The Indonesian Journal of Communication Studies, 2022)
LPP RRI Semarang has a function not only to provide information and entertainment but also to contribute to the preservation of local culture by presenting various cultural arts programs such as "ketoprak". The ketoprak program is one of the flagship programs that have loyal fans. so, to maintain its existence, it is important for a director of the ketoprak program to understand this art. The main obstacle in this program is how a director must think creatively in the production process by utilizing existing resources so that it remains attractive to listeners in today's competition in the radio industry. Thus, a good strategy is needed by the director in the production of the ketoprak program. This research is presented qualitatively with a phenomenological approach where the experience of a director of a ketoprak program is the main focus. The production of the ketoprak program is divided into four stages, namely, Pre-Production, Training, Production, and Post-Production. The director of the ketoprak program was directly involved in all these stages, both ideas, and technical matters. Director In the pre-production process, the director coordinates with the producer and scriptwriter in terms of finding story ideas. The script was implemented in rehearsal by all actors and crew. In the production process, the director is fully responsible for its implementation. Lastly, in post-production, the director leads the evaluation.